Analisis Yuridis Pertanggungjawaban Tindak Pidana Pencurian Ternak dalam Keadaan Memberatkan (Studi Putusan Pengadilan Negeri Kisaran Nomor 694/Pid.B/2021/PN Kis) - Nanda Iskandar Zulkarnain (Jurnal Smart Hukum (JSH), 2022)
The crime of theft is still a dilemma and is a serious problem and requires a solution. The problems in this study are how to regulate criminal law against the crime of livestock theft in the case of the Kisaran District Court Decision Number 694/Pid.B/2021/PN Kis, how is the responsibility of the perpetrators of the crime of livestock theft in aggravating circumstances, how is the judge's legal considerations in the Court's Decision Negeri Kisaran Number 694/Pid.B/2021/PN Kis. This study uses a descriptive method through a normative approach (legal research), namely an approach to problems, carried out by examining various legal aspects in terms of applicable regulations. The results of the research on the criminal law regulation of the crime of livestock theft in the case of the Kisaran District Court Decision Number 694/Pid.B/2021/PN Kis is regulated in Article 363 Paragraph (1) 1st, 3rd 4th and 5th of the Criminal Code. The responsibility of the perpetrators of the crime of theft of livestock in aggravating circumstances is the fulfillment of all the elements in accordance with the articles imposed by the defendants and there is no justification and excuse for the actions committed by the defendants, and it is considered that the defendant is able to account for his actions, then the defendants must take responsibility for their actions. responsible for the actions in accordance with the decision handed down by the Panel of Judges, by serving a prison sentence of 10 (ten) months each.